208 Comparison of BRCA mutation testing in blood and tumour samples from patients with high grade serous ovarian carcinoma. (13th November 2020) - Basha Mohamed, M; Arora, R
Abstract : Introduction: Patients with high grade serous ovarian carcinoma (HGSOC) who harbour BRCA1 and BRCA2 mutations respond better to PARP inhibitor treatment. BRCA mutations can be germline, somatic or both. Germline BRCA mutation is tested on blood samples while testing tumour tissue can detect both somatic and germline mutations. There is no difference in responsiveness to PARP inhibitors between germline and somatic BRCA mutated HGSOC. Methods: We analysed 53 HGSOC patients who underwent both germline BRCA mutation blood testing and formalin fixed paraffin embedded tumour tissue BRCA (tBRCA) mutation testing. Both the tests were performed by Next Generation Sequencing. We compared the incidence of germline and tBRCA mutations. Results: The tBRCA mutation test failed in 19/53 patients (35.8%). Amongst the remaining 34 patients, germline BRCA mutation was detected in 3 patients (8.8%); while 6 patients (17.6%) had a tBRCA mutation. BRCA1 mutation was identified in 3 patients (8.8%). 1 of these cases (33.3%) had a germline mutation and tBRCA was present in all 3 cases (100%). BRCA 2 mutation was present in 3 patients (8.8%), with 2 of these cases (66.7%) being identified as germline mutations and all 3 had tBRCA mutation (100%). While 3 patients (8.8%) had both germline and tBRCA mutations, 3 patients (8.8%) had only tBRCA mutations without germline BRCA mutation which may have been somatic mutations. Conclusion: Our study highlights the importance of performing BRCA mutation testing on both blood and tumour tissue samples in patients with high grade serous ovarian carcinoma.